Bilayer PbS Quantum Dots for High‐Performance Photodetectors. Issue 33 (22nd June 2017) - Ren, Zhenwei; Sun, Jiankun; Li, Hui; Mao, Peng; Wei, Yuanzhi; Zhong, Xinhua; Hu, Jinsong; Yang, Shiyong; Wang, Jizheng
Abstract : Due to their wide tunable bandgaps, high absorption coefficients, easy solution processabilities, and high stabilities in air, lead sulfide (PbS) quantum dots (QDs) are increasingly regarded as promising material candidates for next‐generation light, low‐cost, and flexible photodetectors. Current single‐layer PbS‐QD photodetectors suffer from shortcomings of large dark currents, low on–off ratios, and slow light responses. Integration with metal nanoparticles, organics, and high‐conducting graphene/nanotube to form hybrid PbS‐QD devices are proved capable of enhancing photoresponsivity; but these approaches always bring in other problems that can severely hamper the improvement of the overall device performance. To overcome the hurdles current single‐layer and hybrid PbS‐QD photodetectors face, here a bilayer QD‐only device is designed, which can be integrated on flexible polyimide substrate and significantly outperforms the conventional single‐layer devices in response speed, detectivity, linear dynamic range, and signal‐to‐noise ratio, along with comparable responsivity. The results which are obtained here should be of great values in studying and designing advanced QD‐based photodetectors for applications in future flexible optoelectronics. Abstract : A bilayer lead‐sulfide‐quantum‐dot‐only photodetector is designed, which significantly outperforms conventional single‐layer devices in response speed, detectivity, linear dynamic range, and signal‐to‐noise ratio. Careful investigation finds that junction‐controlled carrier separation and recombination is responsible for the superiority of the bilayer device. The bilayer devices also signal their great potential in future flexible optoelectronics.